1996
DOI: 10.1021/ja953716g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quantum Yield of Poly(p-phenylenevinylene) Prepared via the Paracyclophene Route:  Effect of Chain Length and Interchain Contacts

Abstract: The monomer 9-[(tert-butyldimethylsilyl)oxy][2.2]paracyclophan-1-ene (1) is polymerized by Mo(NAr)(CHCMe2Ph)(OCMe(CF3)2)2 (Ar = 2,6-diisopropylphenyl) in a living manner. Block copolymers containing poly(1) and polynorbornene (poly(NBE)) can be prepared and have narrow polydispersities. Treatment of poly(1) with NBu4F produces poly(9-hydroxy[2.2]paracyclophan-1-ene) which dehydrates to poly(p-phenylenevinylene) (PPV) under mild conditions. Block copolymers containing segments of size-specific and defect-free P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
48
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 38 publications
10
48
0
Order By: Relevance
“…These trends are consistent with recent experimental studies 65,66 showing that highly delocalized conjugated chains do not undergo concentration quenching, as typically observed with dyes; this is why conjugated polymers emerge as highly promising materials for the design of solid-state lasers. 65 III.2.…”
Section: Resultssupporting
confidence: 90%
“…These trends are consistent with recent experimental studies 65,66 showing that highly delocalized conjugated chains do not undergo concentration quenching, as typically observed with dyes; this is why conjugated polymers emerge as highly promising materials for the design of solid-state lasers. 65 III.2.…”
Section: Resultssupporting
confidence: 90%
“…[51] Bazan et al also demonstrated an increase in F f when PPV segments were isolated within a poly(norbornene) matrix. [39] This suggests that the very high quantum yield observed for the PPV@MSS material may be due to the isolation of polymer chains within the mesopores of the silica host. By preventing the formation of interchain excimers, the quantum yield for formation of the fluorescent intrachain excitons is increased.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…A variety of such hosts for PPV have been explored to date. These include porous silica [26][27][28][29][30][31] and alumina, [32] zeolites, [33,34] layered clays, [35,36] amylose, [37,38] poly(norbornene) (PNBE), [39] and vault protein cages. [40] The encapsulated PPV@host materials often possess a variety of properties lacking in the unencapsulated conjugated polymer, including increased fluorescence quantum yield, resistance to photobleaching, liquid crystallinity, and solubility.…”
mentioning
confidence: 99%
“…The polymer containing PPV fragments with various lengths of conjugated and non conjugated segments may be synthesized through par tial conversion of PPV prepared via various methods [7][8][9] or via copolymerization with different flexible spacers [10][11][12]. For example, a random copolymer was described in [10], while blocks copolymers were reported in [11,12]. Note that the size of PPV blocks in these copolymers does not exceed 10 nm [13], that is, the maximum length of diffusion of excitons [14].…”
Section: Introductionmentioning
confidence: 99%